Frequency of Contrast Induced Nephropathy in Patients Undergoing Primary PCI - Afzal , Muhammad; Pervez , Noman; Fazal Ur Rehman; Khan , Abdul Ghaffar; Muhammad Hashim; Bari, Syed Abdul; Kumar, Rawindar; Kakar , Sana Ullah (Indus Journal of Bioscience Research, 2025)
Contrast-induced nephropathy (CIN) is a critical complication of iodinated contrast media used in diagnostic and interventional procedures, particularly primary percutaneous coronary intervention (PCI). This study investigated the incidence of CIN and its associated risk factors in patients undergoing primary PCI. A sample of 120 patients was assessed, with CIN defined as a 25% or 0.5 mg/dL increase in serum creatinine within 48–72 hours post-contrast exposure. The findings revealed a CIN incidence of 15% (n = 18), aligning with reported rates in high-risk populations. Key risk factors identified included diabetes, present in 66.67% of CIN cases, and pre-existing renal impairment (eGFR < 60 mL/min), observed in 55.56% of cases. Hemodynamic instability, marked by hypotensive episodes, was documented in 33.33% of CIN patients, while 77.78% received >200 mL of contrast media, highlighting a dose-dependent risk. Preventive measures such as pre-procedural hydration and the use of low-osmolar contrast agents showed limited efficacy, with only 22.22% of CIN patients adequately hydrated. Adjunctive therapies, including statins and N-acetylcysteine, demonstrated minimal protective effects. The results underscore the need for robust preventive strategies, including stringent hydration protocols and minimizing contrast media usage, particularly in high-risk groups. CIN remains a significant contributor to acute kidney injury and adverse outcomes, emphasizing the importance of targeted risk mitigation and further research into innovative therapeutic interventions. This study highlights the critical role of personalized care approaches in reducing CIN incidence and improving post-PCI outcomes.